2011
DOI: 10.4061/2011/814507
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Biodiesel Synthesis Using a Byproduct Obtained from Palm Oil Refining

Abstract: An alternative route to produce biodiesel is based on esterification of free fatty acids present in byproducts obtained from vegetable oil refining, such as palm oil fatty acid distillate (PFAD). PFAD is a byproduct of the production of edible palm oil, which contains 96 wt.% of free fatty acids. The purpose of this work was to study biodiesel synthesis via esterification of PFAD with methanol and ethanol, catalyzed by commercial immobilized lipases (Novozym 435, Lipozyme RM-IM, and Lipozyme TL-IM), in a solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…The fatty acid ethyl ester (FAEE) content in the reaction medium was determined by gas chromatography according to the method described by Corrêa et al 13 The samples were analyzed on a Varian gas chromatograph (CP-3380 model), equipped with a flame ionization detector (FID), a CP WAX 52 CB capillary column 30 m x 0.25 mm x 0.25 mm, and a split injection system with a 1/20 ratio. Injector and detector temperatures were kept at 280 and 300 °C, respectively.…”
Section: Ester Contentmentioning
confidence: 99%
“…The fatty acid ethyl ester (FAEE) content in the reaction medium was determined by gas chromatography according to the method described by Corrêa et al 13 The samples were analyzed on a Varian gas chromatograph (CP-3380 model), equipped with a flame ionization detector (FID), a CP WAX 52 CB capillary column 30 m x 0.25 mm x 0.25 mm, and a split injection system with a 1/20 ratio. Injector and detector temperatures were kept at 280 and 300 °C, respectively.…”
Section: Ester Contentmentioning
confidence: 99%
“…Biodiesel production using enzyme catalysts is a more environmentally friendly process and reaches adequate or even higher yields than the previously analyzed processes (Rivera et al, 2009;Yujaroen et al, 2009;Joon et al, 2011). Although these processes involving enzymes are costly (Chongkhong et al, 2009;Haas, 2005;Yujaroen et al, 2009;Yan et al, 2010b;Liu and Wang, 2009;Helwani et al, 2009b;Wang et al, 2007), the enzyme-based processes reduce energy cost as well as tend to have lower waste treatment costs (Dos Santos Correa et al, 2011).…”
Section: Heterogeneous and Enzymatic Catalystsmentioning
confidence: 99%
“…Using enzymes, conversion efficiencies between 70-90% for the transesterification reaction can be obtained (Rivera et al, 2009;Haas, 2005;Dos Santos Correa et al, 2011;Juan et al, 2011;Modi et al, 2006). Using lipase, 63% esterification conversion was reported (Haas, 2005) with an overall efficiency of 81%.…”
Section: Heterogeneous and Enzymatic Catalystsmentioning
confidence: 99%
“…In contrast, the use of a temperature of 30 gave a yield of ca. 89 after only 12 h. Correa et al 25 reported that Lipozyme RM IM behaved as a stable and active lipase in anhydrous media but underwent a significant reduction in its activity towards esterification at temperatures above 40 in the presence of low-molecular-weight alcohols. Similar results to these were also obtained in the current study.…”
Section: Temperaturementioning
confidence: 99%
“…Also, Hernández et al reported that the maximum yield obtained with Lipozyme TL IM was much lower than that with Novozym 435 after the esterification of soybean oil with ethanol 24 . The use of an excess of the alcohol substrate led to a reduction in the activity of the enzyme and a decrease in the yield 25 . However, increasing the amount of alcohol in the transesterification reaction, up to a certain amount, could enhance the solubility of the oil in the alcohol, and lead to a higher yield.…”
Section: Molar Ratiomentioning
confidence: 99%